2006
DOI: 10.1037/0012-1649.42.4.723
|View full text |Cite
|
Sign up to set email alerts
|

Precision of imitation as a function of preschoolers' understanding of the goal of the demonstration.

Abstract: The authors argue that imitation is a flexible and adaptive learning mechanism in that children do not always reproduce all of the details they can from a demonstration. Instead, they vary their replications depending on their interpretation of the situation. Specifically, the authors propose that when children do not understand the overall reason for a model's behavior, they will be more likely to imitate precisely. By copying conservatively in these situations, children may have a good chance of reproducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 27 publications
4
81
1
1
Order By: Relevance
“…However, this hypothesis does not obviously predict one of our central findings, namely, the fact that the children showed an overall bias towards the path information. As discussed in the introduction, previous work has found two main situations in which children prefer a non-goal interpretation: when the goal is absent (i.e., there is no visible external outcome of the action) as in Bekkering et ala (2000) and Pulverman et al (in press); and when the non-goal is specially highlighted as in Gergely et al (2002), and Williamson and Markman (2006). We consider next whether one of these situations holds in the current experiment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, this hypothesis does not obviously predict one of our central findings, namely, the fact that the children showed an overall bias towards the path information. As discussed in the introduction, previous work has found two main situations in which children prefer a non-goal interpretation: when the goal is absent (i.e., there is no visible external outcome of the action) as in Bekkering et ala (2000) and Pulverman et al (in press); and when the non-goal is specially highlighted as in Gergely et al (2002), and Williamson and Markman (2006). We consider next whether one of these situations holds in the current experiment.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Nielsen (2006) found that young toddlers were more likely to imitate a specific action with a tool to open a box if they saw that the tool was necessary, and that trying to open the box without the tool would not work. Similarly, Williamson and Markman (2006) found that 3-year-olds were more likely to imitate an unusual action if they were provided with an explanatory context for it. And, in a completely opposite approach, Gergely, Bekkering and Kiraly (2002) found that 14-month-olds infants were much more likely to imitate a particular manner of action (such as turning on a light with their head) when it was an apparently irrational way of accomplishing the goal.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Other work also highlights the role of goals in imitation (Bekkering, Wohlschläger, & Gattis, 2000;Csibra & Gergely, 2007;Elsner, 2007;Gattis, Bekkering, & Wolschläger, 2002;Gleissner, Meltzoff, & Bekkering, 2000;Meltzoff & Moore, 1997;Tomasello et al, 2005;Williamson & Markman, 2006;Wohlschläger, Gattis, & Bekkering, 2003). Our work helps address developmental origins.…”
Section: Implications For Theorymentioning
confidence: 98%
“…Thus the relation between the child's own level of causal understanding and the model's demonstration may be a significant factor in studies of tool-use imitation. It is an example of imitation not being blind or automatic, but rather of prior knowledge influencing what you encode and use from the modeling of others (e.g., Carpenter, Call, & Tomasello, 2002;Gergely, Bekkering, & Király, 2002;Williamson & Markman, 2006).…”
Section: Implications For Theorymentioning
confidence: 99%